Study of Egodocuments: Old Spaces – New Horizons - Pacevičius, Arvydas (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]Based on the analysis of project results, the article discusses the achievements in the study of egodocuments over the past five years and the prospective study fields emerging in the European research area and Lithuania. In Lithuania, attention to egodocuments increased in around 2010 after a new term – egodocument – was introduced to scientific discourse; its conceptual adaptation led to more systematic studies of writings in the first person. In addition to the studies published in the framework of the project Egodocumental Heritage of Lithuania (LEGODOK), the project Creation of the Private Written Lithuanian Language Database (AKdb) implemented by the Institute of the Lithuanian Language and its partners deserves a special mention; in the frames of the project, the data of the written Lithuanian language (letters, diaries, memoirs, inscriptions on photographs) are collected and digitalised electronically. In Lithuania, the general research tendency can be considered the studies on self-consciousness and identity expression of the elite (Radziwiłł, Römer) as well as the attempts to add an increasing number of sources to the research field, e.g. memory books (album amicorum) telling about oneself, i.e. the creating person. Traditionally, the so called ‘from below’ studies focusing on non-elite social groups are strong in Lithuania. They include the research of written culture and mentality change associated with national revival related problems. They consider egodocuments (including letters) and their dissemination in the period of early modernity a public rather than private means of communication. Inter-disciplinary ‘from below’ studies are viable in Northern Europe (Anna Kuismin). In Western Europe the Villa Vignoni forum, bringing together Italian, French and German researchers (Giovanni Ciappelli, François-Josephas Ruggiu, Claudia Ulbrich), inspired solid publications dedicated to personal, familial and communal identities in a cross-cultural perspective. The published egodocumentary history sources and the fundamental research carried out in Poland often extend to the issues of old Lithuania (Adam Kucharski, Stanisław Roszak). Therefore, with certain research tendencies coming to the fore, the article makes a conclusion that by expanding international cooperation with our neighbours, the research of the egodocumentary heritage of Lithuania as expression of linguistic identity as well as cross-cultural research of multilingualism and dissemination of multidimensional identity in the modernising society should be continued in Lithuania.